Polarization-independent holographic gratings based on azo-dye-doped polymer-dispersed liquid-crystal films - Fuh, Andy Ying-Guey; Chen, Che-Chang; Cheng, Ko-Ting; Liu, Cheng-Kai; Chen, Wei-Ko (Applied optics. Optical technology and biomedical optics, 2010)
We demonstrate polarization-independent holographic gratings (PIHGs) based on azo-dye-doped polymer-dispersed liquid crystal films. The PIHGs are recorded by irradiation under an intensity-modulated interference field, generated by two linearly polarized green optical beams, and by simultaneously applying a suitable AC voltage to the sample. The photoexcited azo dyes are adsorbed onto the UV-cured polymer film with their long axes parallel to the normal of the substrate. When the applied voltage is switched off, the PIHGs are generated with periodic modulation of liquid-crystal structures with transparently homeotropic and randomly scattered alignments. Additionally, the generated PIHGs can be completely switched off by an applied voltage.